A Full‐Stokes 3‐D Calving Model Applied to a Large Greenlandic Glacier. Issue 3 (1st March 2018) - Todd, Joe; Christoffersen, Poul; Zwinger, Thomas; Råback, Peter; Chauché, Nolwenn; Benn, Doug; Luckman, Adrian; Ryan, Johnny; Toberg, Nick; Slater, Donald; Hubbard, Alun
Abstract: Iceberg calving accounts for around half of all mass loss from both the Greenland and Antarctic ice sheets. The diverse nature of calving and its complex links to both internal dynamics and climate make it challenging to incorporate into models of glaciers and ice sheets. Here we present results from a new open‐source 3‐D full‐Stokes calving model developed in Elmer/Ice. The calving model implements the crevasse depth criterion, which states that calving occurs when surface and basal crevasses penetrate the full thickness of the glacier. The model also implements a new 3‐D rediscretization approach and a time‐evolution scheme which allow the calving front to evolve realistically through time. We test the model in an application to Store Glacier, one of the largest outlet glaciers in West Greenland, and find that it realistically simulates the seasonal advance and retreat when two principal environmental forcings are applied. These forcings are (1) submarine melting in distributed and concentrated forms and (2) ice mélange buttressing. We find that ice mélange buttressing is primarily responsible for Store Glacier's seasonal advance and retreat. Distributed submarine melting prevents the glacier from forming a permanent floating tongue, while concentrated plume melting has a disproportionately large and potentially destabilizing effect on the calving front position. Our results also highlight the importance of basal topography, which exerts a strong control on calving, explaining why Store Glacier has remained stable during a period when neighboring glaciers have undergone prolonged interannual retreat. Plain Language Summary: Most freshwater on our planet is stored as ice in the ice sheets of Greenland and Antarctica. The ice sheet in Greenland is currently losing mass at a rate that is equal to 1 mm/year of sea level rise. Around half of the ice loss in Greenland is lost through icebergs released into the sea through a process called "calving." Iceberg calving is poorly understood and has so far not been included in 3‐D models needed to predict sea level rise. Recent studies show that warming of the air and ocean is linked to more calving, but we still do not understand these links sufficiently to make predictions. This study presents a new computer model, which is the first to simulate glacier flow and iceberg calving in 3‐D, and investigates calving at Store Glacier in Greenland. We test the model by reproducing the present‐day seasonal cycle of the glacier and find that fractures forming on the surface as well as the bottom of the glacier control the calving rate. We show that the calving rate is influenced by submarine melting of the calving ice front as well as by ice mélange, which is a mixture of icebergs and sea ice forming in front of the glacier in winter. Key Points: A 3‐D full‐Stokes calving model was implemented in Elmer/Ice and applied to Store Glacier in West Greenland The model reproduces the seasonal characteristics of ice flow and calving without tuning Ice mélange and submarine melting link calving to the ocean, strongly modulated by basal topography